Evaluación del rendimiento del cultivo de la mashua (tropaeolium tuberosum) a tres dosis de fertilizantes edáficos y tres bioestimulantes - Chamorro Melo, Klever Orlando (2017)
VIII. SUMMARY This research was conducted in the Struts community Bajo, Canton Bolivar, Bolivar parish in the province of Carchi. The area is located 008'29,92 "north latitude, 77042'35" west latitude and at an altitude of 2600 meters. The area has climatic characteristics with annual averages of humid temperate climate with average annual temperature of 14 0C and a relative humidity of 81%. Mashua seed tubers (Tropaeoleum tuberosum) from black variety of the study area were used. The objectives were to evaluate the effect of soil and fertilization bioestimulantes agronomic performance culture mashua, determine the appropriate dose of fertilizer for growing and economically analyze treatments. The treatments were composed by doses of soil based fertilizers Nitrogen, phosphorus and potassium in doses of 120-300-240; 80-200-160; 40-100-160 kg / ha and bioestimulantes Bio-Stim, Bio-Bio-Energy Zime and more an absolute control. Design Randomized Complete Block (DBCA) with ten treatments and three replications was used. Comparisons of averages were carried out by testing ranges Duncan minimum 5% probability. Crop development for the preparatory work of the experimental field, delimitation of the plots, planting, fertilizing, weeding and hoeing, foliar application of bio-stimulants, irrigation, pest and disease control and harvesting were made. To estimate the effects of treatment data germination percentage, days to flowering, plant length, days to maturity, performance by category and economic analysis were evaluated. For the results presented, it was determined that the doses of soil fertilizer, combined with three bioestimulantes favorable results in crop yield mashua (Tropaeolum tuberosum); all treatments obtained excellent germination percentage; the absolute control was the treatment that took to blossom and mature; the application of 40 kg / ha of N + 100 kg / ha of P + 160 kg / ha of K with bioestimulante Bio - Zime reported longer plant at 60 and 90 days and the increased crop yield and net profit as got the application of 40 kg / ha of N + 100 kg / ha of P + 160 kg / ha of K using the Bio-Energy bioestimulante 17333.3 kg / ha and $ 5603.89.